Two tales the iron wall & the queen of egypt - Khan, Saniyasnain (Goodword Books India, 2002)
These stories explore themes of resilience and leadership, where the iron wall represents steadfastness in faith, and the Queen of Egypt embodies wisdom and strength in guiding her people.